2009
DOI: 10.1210/en.2008-1613
|View full text |Cite
|
Sign up to set email alerts
|

Cathepsin L Colocalizes with Chromogranin A in Chromaffin Vesicles to Generate Active Peptides

Abstract: Chromogranin A (CgA), the major soluble protein in chromaffin granules, is proteolytically processed to generate biologically active peptides including the catecholamine release inhibitory peptide catestatin. Here we sought to determine whether cysteine protease cathepsin L (CTSL), a novel enzyme for proteolytic processing of neuropeptides, acts like the well-established serine proteases [prohormone convertase (PC)1/3 or PC2] to generate catestatin by proteolytic processing of CgA. We found that endogenous CTS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(54 citation statements)
references
References 60 publications
0
52
0
2
Order By: Relevance
“…Results here indicate the presence of cathepsin V in neuronal tissue regions that is compatible with its unique role in the production of enkephalin and NPY peptide neurotransmitters. The findings from this study of human cathepsin V and from prior studies of cathepsin L (mouse, bovine, and human) indicate their role in processing dibasic residue sites of proprotein precursors in secretory vesicles for the production of neuropeptides (1)(2)(3)(4)(5)(6)(7)36). Both cathepsin V and cathepsin L show cleavage of proneuropeptides at the N-terminal side of dibasic processing sites (i.e.…”
Section: Substratementioning
confidence: 56%
See 2 more Smart Citations
“…Results here indicate the presence of cathepsin V in neuronal tissue regions that is compatible with its unique role in the production of enkephalin and NPY peptide neurotransmitters. The findings from this study of human cathepsin V and from prior studies of cathepsin L (mouse, bovine, and human) indicate their role in processing dibasic residue sites of proprotein precursors in secretory vesicles for the production of neuropeptides (1)(2)(3)(4)(5)(6)(7)36). Both cathepsin V and cathepsin L show cleavage of proneuropeptides at the N-terminal side of dibasic processing sites (i.e.…”
Section: Substratementioning
confidence: 56%
“…The unique nature of cathepsin V in the human genome raises the issue of the biological function of human cathepsin V with that of the highly homologous human cathepsin L. Notably, results of this study with others (7,36) in the field indicate the joint roles of human cathepsin V and human cathepsin L for proneuropeptide processing. However, in contrast to the human genome, the genomes of mouse and other mammals (bovine, sheep, and others) encode only cathepsin L but not orthologues of cathepsin V (8 -11).…”
Section: Substratementioning
confidence: 65%
See 1 more Smart Citation
“…It is generated from chromogranin A (CHGA) (Biswas et al, 2009;Helle, 2010), a major protein costored and co-released with catecholamines from secretory granules of chromaffin cells and adrenergic neurons (Sahu et al, 2010;Taupenot et al, 2003). Although CHGA is overexpressed in genetic hypertension (Friese et al, 2005;O'Connor et al, 1999;Takiyyuddin et al, 1995), the plasma CST level is diminished not only in established hypertensive patients but also in their normotensive offspring .…”
mentioning
confidence: 99%
“…More recently, it was shown that cathepsin L colocalizes with CGA in chromaffin granules. In vitro it is able to generate after digestion of recombinant hCGA, a catestatin (CAT)-derived fragment hCGA360-373 (Biswas et al, 2009). In addition to the inhibitory effect of CAT on catecholamine release from chromaffin cells (Mahata et al, 1997), we have shown for this peptide and its shorter active sequence bCGA344-358 (cateslytin, CTL), (Figure 3) a potent antimicrobial activity with a MIC in the lowmicromolar range against Gram-positive bacteria (Micrococcus luteus, Bacillus megaterium at concentration of 0.8 µM), Gram-negative bacteria (Escherichia coli D22 at concentration of 8 µM), filamentous fungi (Neurospora crassa, Aspergillus fumigatus, Nectria haematococca at concentration of 0.2-10 µM) and yeasts (Candida albicans, Candida tropicalis, Candida glabrata, Candida neoformans at concentration of 1.2-8 µM).…”
Section: Catestatinmentioning
confidence: 99%